Use of TOPSIS method for assessing of good governance in European Union countries - Eva Ardielli (Review of Economic Perspectives, 2019)
Good Governance presents the contemporary trend of managing public affairs worldwide. This concept is promoting the basic elements of subsidiarity, participation, and democracy in modern public administration. Presented article is focused on the evaluation of Good Governance development in the European Union countries in the long-term, in the period 2007-2017. The evaluation is based on the application of multiple criteria decision-making methods, concrete The Technique for Order Preference by Similarity to Ideal Solution. The original data used in the research were the values of Worldwide Governance Indicators monitored and processed by the World Bank. The article presents a complete assessment of European Union countries according to the level of Good Governance. There are identified countries that have been successful in this area in the long-term, in particular the Nordic countries - Finland, Sweden and Denmark. On the contrary, there are countries that show greater shortcomings in terms of Good Governance as Romania, Bulgaria or Greece. The European Union countries were also grouped into clusters and the overview of rankings of individual countries for the period 2007-2017 was completed.
Keywords: H11; H83; 330; European Union countries; evaluation; good governance; governance indicators